THE FUTURE OF HIGHER EDUCATION - Ishomuddin, Ishomuddin (Jurnal Bestari, 1993)
The system of education has some components  such as lacturers, students, curriculum, education resources, administrators and leaders of institution. Those components interact and proceed to achieve the goals. If one wants to develop the quality of education, he must improve and control all components. In the information era, the role of high education become more important, because the qualified education can provide skilful young generation who are able to participate in developing country.